The effects of ionic surfactants on expanding free surfaces - White, A (University of Oxford;Mathematical Institute, 2001)
This study is based upon the `overflowing cylinder' experiment and develops an ionic theory for the advection-diffusion dynamics of surfactant in this experiment. It is hoped that a consideration of these ionic effects can account for discrepancies between theoretical and experimental results for the overflowing cylinder. We begin by describing in detail the general fluid and surfactant dynamics and produce a model for this ionic system. We apply the model to a range of different problems to gain an understanding of the ionic effects. Finally, we address the original nonionic model presented for the analysis of the overflowing cylinder experiment and decipher a parameter missing from some papers which study this experiment.